Process Optimization of L-Phenylalanine onto Porous Silica Nanoparticles - Tan, Suat Hian; Nurul Ain, Ismail (Trans Tech Publications, 2014)
Porous silica nanoparticles play an important role in the field of bioseparations and biomedical applications by offering large surface area and pore volume for adsorption of solutes. The present work deals with the synthesis, characterization and adsorption studies on silica nanoparticles. The nanoparticles were synthesized using tetraethylorthosilicate as starting material and ethanol as solvent by sol-gel method under basic medium. Subsequently, L-phenylalanine was loaded into these nanoparticles by simple adsorption and the adsorption capacity was examined by UV spectrophotometer at 257 nm. The different operating parameters such as pH, silica nanoparticles dosage and duration on the uptake of the L-phenylalanine were studied. The results indicate the potential for a new use of silica nanoparticles as an effective adsorbent for Lphenylalanine.